2019
DOI: 10.3390/sym11020176
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Word-Based Algorithmically Generated Domains Using Semantic Analysis

Abstract: In highly sophisticated network attacks, command-and-control (C&C) servers always use domain generation algorithms (DGAs) to dynamically produce several candidate domains instead of static hard-coded lists of IP addresses or domain names. Distinguishing the domains generated by DGAs from the legitimate ones is critical for finding out the existence of malware or further locating the hidden attackers. The word-based DGAs disclosed in recent network attack events have shown significantly stronger stealthiness wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Schales et al [14] performed detection by extracting 17 domain name features combined with four of weighted confidence and verified the effectiveness of the algorithm in a large-scale network environment. Yang et al [15] proposed a word semantic analysis method for word-based domain names to detect malicious domain names by the correlation between words in them. e drawback of feature-based detection algorithms is that they rely on manual feature analysis capabilities, and the dimensionality of character-level features is limited.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Schales et al [14] performed detection by extracting 17 domain name features combined with four of weighted confidence and verified the effectiveness of the algorithm in a large-scale network environment. Yang et al [15] proposed a word semantic analysis method for word-based domain names to detect malicious domain names by the correlation between words in them. e drawback of feature-based detection algorithms is that they rely on manual feature analysis capabilities, and the dimensionality of character-level features is limited.…”
Section: Related Workmentioning
confidence: 99%
“…e segmentation method used in step 1 is the bidirectional maximum matching algorithm [15]. A unique parsing result T s ′ � e 1 , e 2 , .…”
Section: Adaptive Embedding Modulementioning
confidence: 99%
“…Another approach in [59], proposed a framework for identification word-based DGAs by utilizing the frequency distribution of the words and an ensemble classifier constructed from naive Bayes, extra-trees, and logistic regression. The authors reported that their method outperformed the comparable ones.…”
Section: Identifying Domain Names Generated By Dgasmentioning
confidence: 99%
“…Yang et al. [ 19 ] analyzed several types of features including word frequency, parts-of-speech, inter-word correlation, and inter-domain correlations by bi-directional maximum matching and then built an ensemble classifier to identify algorithmically generated domain names. Li et al.…”
Section: Related Workmentioning
confidence: 99%